2020
DOI: 10.1002/jsfa.10221
|View full text |Cite
|
Sign up to set email alerts
|

Sensory properties of yellow pea and macadamia honeys from conventional and flow hive extraction methods

Abstract: BACKGROUND The process of harvesting honey is time consuming and labor intensive. A new system, the Flow Frame, has drastically simplified the harvesting process, enabling honey to be extracted directly from the hive with minimal processing. The sensory profile of honey is influenced, first, by botanical origin and subsequently by processing and storage parameters. A reduction in harvest processing may thus influence the sensory profile of honey harvested from FFs compared to that of honey produced from conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The analytical methods, the sensory evaluation of honey can complement the confirmation of the botanical origin, establish sensory profiles for monofloral honey, verify quality, among others [ 118 ], since various studies have observed differences in the characteristics of honeys according to their floral and geographical origin [ 50 , 60 , 119 , 120 , 121 ]…”
Section: The Color Of the Honey And Phenolic Compoundsmentioning
confidence: 99%
“…The analytical methods, the sensory evaluation of honey can complement the confirmation of the botanical origin, establish sensory profiles for monofloral honey, verify quality, among others [ 118 ], since various studies have observed differences in the characteristics of honeys according to their floral and geographical origin [ 50 , 60 , 119 , 120 , 121 ]…”
Section: The Color Of the Honey And Phenolic Compoundsmentioning
confidence: 99%
“…In other words, the differences in bran , herbaceous , green vegetable , and green fruit between the different halophyte‐based test foods were not apparent for some panelists as it was for others. This could be caused by differences in the individual threshold levels (“below or above”) (Grace et al., 2020). However, this did not compromise the work of the panelists and subsequently the validity of the generated sensory results.…”
Section: Resultsmentioning
confidence: 99%
“…An initial benchtop tasting session was conducted previously described by Grace et al. (2020) with slight modifications. Six experienced tasters, five females and one male aged between 28 and 56 years, participated in the two sessions (2 h each).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Grace et al (2019) showed significant differences in the sensorial acceptance of honeys harvested with the conventional and flow frame techniques. The latter innovative method allows honey to flow down to a collection vessel, without centrifugation and filtration steps.…”
Section: Results Of Sensory Profile Analysis Of Multiflorous Linden and Buckwheat Honey Samplesmentioning
confidence: 99%